Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the equation given by the problem, we need to translate it into algebraic form and solve for the variable [tex]\(d\)[/tex].
1. Translate the problem into an equation:
The difference of [tex]\(-2d\)[/tex] and [tex]\(-3d\)[/tex] can be written as:
[tex]\[ \text{Difference of } -2d \text{ and } -3d = -2d - (-3d) \][/tex]
The difference of [tex]\(\frac{1}{6}\)[/tex] and [tex]\(\frac{1}{3}\)[/tex] can be written as:
[tex]\[ \text{Difference of } \frac{1}{6} \text{ and } \frac{1}{3} = \frac{1}{6} - \frac{1}{3} \][/tex]
Now we set these two expressions equal to each other:
[tex]\[ -2d - (-3d) = \frac{1}{6} - \frac{1}{3} \][/tex]
2. Simplify the left-hand side:
Simplifying the left-hand side:
[tex]\[ -2d - (-3d) = -2d + 3d = d \][/tex]
3. Simplify the right-hand side:
Simplifying the right-hand side:
[tex]\[ \frac{1}{6} - \frac{1}{3} \][/tex]
To subtract these fractions, we need a common denominator. The least common denominator for 6 and 3 is 6.
[tex]\[ \frac{1}{3} = \frac{2}{6} \][/tex]
So,
[tex]\[ \frac{1}{6} - \frac{2}{6} = \frac{1 - 2}{6} = \frac{-1}{6} \][/tex]
4. Equate both sides and solve for [tex]\(d\)[/tex]:
Now, we have:
[tex]\[ d = \frac{-1}{6} \][/tex]
5. Check the solution:
Substitute [tex]\(d = \frac{-1}{6}\)[/tex] back into the equation to verify:
[tex]\[ -2 \left( \frac{-1}{6} \right) - (-3 \left( \frac{-1}{6} \right)) = \frac{1}{6} - \frac{1}{3} \][/tex]
Simplifying the left-hand side:
[tex]\[ -2 \left( \frac{-1}{6} \right) + 3 \left( \frac{-1}{6} \right) = \frac{2}{6} - \frac{3}{6} = \frac{-1}{6} \][/tex]
Both sides of the equation are equal, confirming that our solution is correct.
Thus, the solution is:
[tex]\[ d = -\frac{1}{6} \][/tex]
1. Translate the problem into an equation:
The difference of [tex]\(-2d\)[/tex] and [tex]\(-3d\)[/tex] can be written as:
[tex]\[ \text{Difference of } -2d \text{ and } -3d = -2d - (-3d) \][/tex]
The difference of [tex]\(\frac{1}{6}\)[/tex] and [tex]\(\frac{1}{3}\)[/tex] can be written as:
[tex]\[ \text{Difference of } \frac{1}{6} \text{ and } \frac{1}{3} = \frac{1}{6} - \frac{1}{3} \][/tex]
Now we set these two expressions equal to each other:
[tex]\[ -2d - (-3d) = \frac{1}{6} - \frac{1}{3} \][/tex]
2. Simplify the left-hand side:
Simplifying the left-hand side:
[tex]\[ -2d - (-3d) = -2d + 3d = d \][/tex]
3. Simplify the right-hand side:
Simplifying the right-hand side:
[tex]\[ \frac{1}{6} - \frac{1}{3} \][/tex]
To subtract these fractions, we need a common denominator. The least common denominator for 6 and 3 is 6.
[tex]\[ \frac{1}{3} = \frac{2}{6} \][/tex]
So,
[tex]\[ \frac{1}{6} - \frac{2}{6} = \frac{1 - 2}{6} = \frac{-1}{6} \][/tex]
4. Equate both sides and solve for [tex]\(d\)[/tex]:
Now, we have:
[tex]\[ d = \frac{-1}{6} \][/tex]
5. Check the solution:
Substitute [tex]\(d = \frac{-1}{6}\)[/tex] back into the equation to verify:
[tex]\[ -2 \left( \frac{-1}{6} \right) - (-3 \left( \frac{-1}{6} \right)) = \frac{1}{6} - \frac{1}{3} \][/tex]
Simplifying the left-hand side:
[tex]\[ -2 \left( \frac{-1}{6} \right) + 3 \left( \frac{-1}{6} \right) = \frac{2}{6} - \frac{3}{6} = \frac{-1}{6} \][/tex]
Both sides of the equation are equal, confirming that our solution is correct.
Thus, the solution is:
[tex]\[ d = -\frac{1}{6} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.